Predictions of HF system performance for propagation through disturbed ionospheres measured using low‐Earth‐orbit satellite radio beacon tomography - Bernhardt, Paul A. (2014)
The CERTO radio beacon on the C/NOFS satellite sends VHF/UHF radio signals at 150 and 400 MHz to provide measurements of integrated electron density or Total Electron Content (TEC) by an east‐west chain of ground receivers in Peru. Computerized Ionospheric Tomography (CIT) is used to convert the TEC data into two‐dimensional images of electron densities with maximum 5 × 5 km resolution in Longitude‐Altitude space. These images are updated every 95 min as the C/NOFS satellite passes over the receiver network in its low‐latitude orbit with an inclination of 12°. The 2‐D, high‐resolution images of the ionosphere are used to predict the impact of equatorial plasma structures on HF propagation of radar and radio signals. Electron density measurements from the NRL radio tomography chain across Peru are used for simulations of the performance by HF one‐way links. HF rays from transmitter to receiver are traced through the electron density images produced by radio beacon tomography. Eight separate paths are found between a transmitter and ground receiver separated by 2000 km. A total of 36 backscatter echoes are found with unique group delay, Doppler frequency shift, phase delay, and echo amplitude. This multipath effect explains the range and Doppler spreading of observations for HF monostatic radar propagation through F layer irregularities. This type of analysis is useful for prediction and interpretation of range and Doppler observations from HF systems including over‐the‐horizon and SuperDARN radars, HF Geolocation Arrays, and HF communications networks.